Faktor-Faktor Minat Baca Buku Pengembangan Diri - Dwi Aulia Rachmadi Putri; Putri Ayu Aprilianti (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
Referring to the Nielsen BookScan ICM report, sales of self-development genre books at the global level until the weekend in July 2020 (YTD) experienced quite significant growth. This indicates an increasing interest in reading self-development books. However, the discussion regarding reading interest has so far been limited to factors in general. This study aims to determine the factors of reading interest in self-development books. This study used a qualitative method, with a case study approach. Data were collected through semi-structured interview techniques to 6 (six) informants. The data analysis technique used in this research is content analysis, using member checking as a data validity technique. The results of this study found several other factors of interest in reading self-development books, namely academic demands, experiences of body shaming and bullying, character modeling, social media algorithms, and others. The implication of this research is to enrich knowledge by specifying the reading interest factor in self-development books.